SPIRAL COMPUTED TOMOGRAPHY IN DETERMINING THE PARAMETERS OF LAPAROTOMY TO THE ABDOMINAL ORGANS - Иван Юрьевич Данильченко; Юрий Борисович Развозжаев; Ярослав Миронович Лещишин; Илья Васильевич Савостьянов; Андрей Владимирович Алонцев (Медицина в Кузбассе)
Objective – to justify the use of spiral computed tomography in determining the parameters of laparotomy to the abdominal organs.